World history from the ancient world to the information age - Parker, Philip 1965- (DK, 2020)
A truly global view of history covering over 350 of the world's most important milestones and key turning points. An essential gift for every history buff, this boldly illustrated book maps out the events that have shaped our world - from the dawn of human civilization to the present day. A comprehensive and accessible guide to the history of human civilisation, World History profiles everything from the emergence of Homo Sapiens to the Greek and Roman empires, through Chinese dynasties, the rise of the Vikings, and the Renaissance, to the Industrial Revolution and World War I and II. Offering a concise and insightful overview of key historical milestones that have occurred over the course of the last century, the book also covers more recent events such as the rise of ISIS, the Arab Spring, and Brexit and populism in the Western world.